E Evaluasi Penerapan Standar Pelayanan Kefarmasian Di Puskesmas Kecamatan Parenggean - Rahmah, Aulia; Yuwindry, Iwan; Komaliya, Risyda (LPPM Universitas Sari Mulia, 2024)
Background: Some remote areas often face their own challenges in terms of access and quality of pharmaceutical services, the role of pharmacists and pharmaceutical personnel in the Community Health Center is still a question. Based on this, the researcher is very interested in knowing how the implementation of pharmaceutical services in the Community Health Center in the researcher's place of origin, namely the Community Health Center in Parenggean District.Objective: The purpose of this study is to observe in depth the implementation of pharmaceutical service standards at the Parenggean I Health Center and the Parenggean II Health Center based on the Indonesian Minister of Health Regulation number 74 of 2016 and the Indonesian Minister of Health Regulation number 26 of 2020.Methods: The methods used were observation and in-depth interviews conducted directly with pharmacists by submitting observation sheets containing questions to obtain information regarding the Management of Pharmaceutical Preparations and Disposable Medical Materials, Clinical Pharmacy Services, Human Resources and Facilities and Infrastructure.Results: There are two Health Centers in Parenggean District. All health centers have implemented the Management of Pharmaceutical Supplies and Disposable Medical Materials in accordance with Permenkes number 74 of 2016, but in terms of Clinical Pharmacy Services, it has not been fully implemented such as patient visits because the two Health Centers do not have inpatient rooms.Conclusion: Pharmaceutical services at Parenggean I Health Center reached 96% and Parenggean II Health Center reached 100% in accordance with Minister of Health Regulation number 74 of 2016 and Minister of Health Regulation number 26 of 2020. These values ​​indicate that overall both Health Centers have met the standards with a good category in providing pharmaceutical services in their working areas